Comprehension of the Presupposition Trigger Ye “Also” by Mandarin-Speaking Preschoolers With and Without Autism Spectrum Disorders - An, Shasha; Bill, Cory; Yang, Qi (Frontiers in Psychology, 2020)
Individuals with Autism Spectrum Disorders (ASD) have been reported to be widely impaired in their understanding of linguistic expressions that rely on elements of the context or norms of communication. The accurate interpretation of sentences conveying presuppositions often relies on such content, however, little previous research has investigated the ASD population’s understanding of these sentences. The present study attempts to remedy this by exploring the understanding that Mandarin-speaking preschoolers with ASD and their typically developing peers have of sentences containing the presupposition trigger ye “also”. We used a Picture Selection Task and found that Mandarin-speaking preschool children with ASD performed significantly worse than their TD peers with regard to their understanding of the presuppositional content of sentences containing this presupposition trigger. Additionally, in contrast with previous results, TD preschoolers’ understanding of this presupposition trigger was found to be adult-like. We attribute this to an improved experimental design.